Agribusiness Product Marketing Analysis: Opportunities and Challenges in the Digital Era - Tri Waluyo (SEAN Institute, 2023)
Digital transformation has impacted various sectors including agribusiness, with changes in consumer behavior patterns, digital marketing technology and increasingly easy access to information through online platforms. This research aims to investigate and analyze the dynamics of marketing agribusiness products in facing the opportunities and challenges that arise in the digital era. This research uses a qualitative approach. The results of this research indicate that agribusiness actors need to actively adopt digital marketing strategies to optimize market potential in the digital era. The findings emphasize that success in agribusiness marketing depends not only on increasing global market access through online platforms, but also on the ability to build consumer trust. A focus on product quality, sustainability practices and transparency in business communications are key to gaining and retaining consumer support. Challenges such as limited access to technology and consumer data protection were also identified as areas requiring serious attention. Therefore, the research recommendations highlight the importance of investing in technology infrastructure, digital skills training, and compliance with privacy regulations to create a successful digital marketing environment in the agribusiness industry.